2017
DOI: 10.1002/ceat.201700005
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Wire‐Mesh Sensor for the Study of Chemical Species Conversion in a Bubble Column

Abstract: The utilization of a wire-mesh sensor for the measurement of chemical species conversion during the chemical adsorption of carbon dioxide in sodium hydroxide solution is reported for the first time. The wire-mesh sensor obtains cross-sectional images of the liquid-phase conductivity, which changes with the consumption of hydroxide during the reaction. A theoretical model was applied to verify the use of conductivity as an indicator for the reaction progress. Experiments were carried out using a lab-scale bubbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…This way, gas can be distinguished from the liquid to study the gas‐liquid flow morphology. Moreover, conductivity tracers can be added to study liquid mixing , . The spatial resolution of WMSs depends on the application and is usually in the range of 3 – 5 · 10 −3 m for pipe flows and 5 – 10 · 10 −3 m for larger bubble columns.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…This way, gas can be distinguished from the liquid to study the gas‐liquid flow morphology. Moreover, conductivity tracers can be added to study liquid mixing , . The spatial resolution of WMSs depends on the application and is usually in the range of 3 – 5 · 10 −3 m for pipe flows and 5 – 10 · 10 −3 m for larger bubble columns.…”
Section: Methodsmentioning
confidence: 83%
“…Subsequently, bubble detection algorithms are applied to extract single bubbles for the calculation of a bubble size distribution. More details on WMS applications and data post‐processing can be found elsewhere , . It was further shown that both measurement techniques provide consistent results .…”
Section: Methodsmentioning
confidence: 83%
“…For further progress in evaluating the chemical differences when varying the solvent or the system, which is activated or changed by the gas, the basic environment of the actual multiphase system should be investigated first. Interesting factors like the bubble velocities, sizes and rising behaviour is usually measured in a water/CO 2 system …”
Section: Systems With Co2mentioning
confidence: 99%
“…Rising bubbles in a bubble column can also be measured by a wire‐mesh sensor as shown by Kipping et al A setup was built to analyse changes in conductivity at different heights of the column with CO 2 bubbles rising in the column through the wire‐mesh measurement planes (Figure ). This conductivity changes occur through the reaction shown in Scheme .…”
Section: Systems With Co2mentioning
confidence: 99%
“…In der Vergangenheit wurden Gittersensoren bereits häufig zur Untersuchung von Strömungsphänomenen in Blasensäulen eingesetzt, bspw. zur Messung von lokalen und integralen Gasgehalten im Querschnitt sowie radialen Gasgehaltsprofilen , zur Aufklärung der Flüssigkeitsrückvermischung oder zur Messung der Stoffumwandlung bei der chemischen Absorption von CO 2 .…”
Section: Introductionunclassified